Role Awareness Training in Student Athletes : Does Awareness of Roles Improve Self Regulation? - Makiko, Noraya Rahma; Jannah, Miftakhul (Jurnal Pendidikan Kesehatan Rekreasi, 2024)
Self-regulation can help student-athletes in achieving goals related to their role as athletes or students. Previous research has shown that role awareness training can improve psychological well-being, but the effect of this intervention on self-regulation has yet to be discovered. This research aims to determine the effect of role awareness training on student-athletes in the SLOMPN Unesa dormitory. The method used is quantitative experimental with a pretest-posttest control group design. The experiment lasted in 4 meetings and was conducted on 12 student-athletes aged 13-16 who were obtained through saturated sampling. Data was obtained through the pretest and posttest of the self-regulation instrument, which was then calculated using the independent t-test method. The results of this study indicate that role awareness training influences student athletes' self-regulation, with a t value of 2,493 and p<0,05. Student-athletes in this study also had equally high autonomous and controlled regulation tendencies.